PENERAPAN MODEL PEMBELAJARAN TEAM GAMES TOURNAMENT BERBANTUAN MEDIA WORDWALL UNTUK MENINGKATKAN KEAKTIFAN DAN PRESTASI BELAJAR PPKN KELAS IV DI SD NEGERI 1 KARANGGINTUNG: Penelitian Tindakan Kelas - Rosalia Yustianawati; Agung Nugroho (STKIP Subang, 2024)
This research is a class action research that focuses on increasing the activeness and completeness of PPKN learning of fourth grade students of SD Negeri 1 Karanggintung. Data were obtained using observation and tests, the data were analyzed quantitatively and qualitatively. The results of the study prove that applying the TGT type cooperative learning model can increase student activeness and learning completeness. The results of the data obtained stated that the completeness of learning in cycle I obtained 54.68% of the criteria was quite good. In cycle II, 82.81% was obtained with very good completeness competency. The results of the observation of learning activeness in cycle I with the average number 2.50 with good competence. In cycle II, the process of learning activeness increased with an average of 3.30 with very good competence.